Pemberian Isometric Exercise Berpengaruh Terhadap Peningkatan Aktivitas Fungsional Pasien Dengan Gangguan Osteoarthritis Genu di RSUD dr. H. Moh. Anwar Sumenep - Asriyanah, Asriyanah; Halimah, Nurul; Wardoyo, Pospo; Pradita, Angria (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:  Osteoarthritis Genu is a long-term chronic disease that causes by pain in the knee and spasm of the quadriceps muscle resulting in decreased functional activity. One of the causes of genu osteoarthritis is degenerative factors. The study was conducted on a sample of 20 people, all of whom were women with an age range of 50-69 years who met the inclusion criteria, namely having complaints of decreased functional activity, the treatment was given 8 times on 6 September-5 October 2021 at dr. H. Moh. Anwar Sumenep with isometric exercise treatment. With the provision of these exercises, patients benefit, namely there is an increase in functional activity.Methods:  The design of this study was experimental with a pre-and post-test design approach without comparison group. In this study, the research subject group, which consisted of 20 people aged between 50-69 years, was given isometric exercise treatment 2 times a week for 4 weeks. Measurement of functional ability in genu OA patients was carried out using the WOMAC scale both before and after treatmentResults: The significance value of the Wilcoxon Ranks test is 0,000 < α (0,05), than there is an effect of isometric exercise in increasing functional activities of knee OA at RSUD dr. H. Moh. Anwar SumenepConclusion:  Based on the data, it can be seen that the average value of functional activity ability before the isometric exercise treatment in OA Genu is 63.44, with a standard deviation of 9.3. After the treatment of isometric exercise 46.71 with a standard deviation of 7.1. According to the WOMAC scale, the value of 46.71 is included in the mild category, because it is less than 60.